Simultaneous quantification and pharmacokinetic evaluation of roflumilast and its N‐oxide in cynomolgus monkey plasma by LC–MS/MS method. (7th September 2020) - Qu, Haijun; Zhang, Keyu; Fu, Chunqing; Qiu, Feng
Abstract: Roflumilast (ROF), a nonsteroidal anti‐inflammatory drug, has successfully been used to treat systemic and pulmonary inflammation associated with chronic obstructive pulmonary disease. To evaluate its pharmacokinetics in monkeys, a sensitive, rapid and reliable liquid chromatography with tandem mass spectrometry (LC–MS/MS) method was developed for the simultaneous determination of ROF and its N‐oxide metabolite (RNO). The mobile phase contained 0.1% formic acid aqueous solution (A) and 0.1% formic acid acetonitrile solution (B). All monkey plasma samples were pretreated using protein precipitation with methanol–acetonitrile (50:50, v/v) in 50 μl plasma samples. Chromatographic separation was performed with mass spectral acquisition performed in positive electrospray ionization, utilizing multiple reaction monitoring. This method was successfully applied to a pharmacokinetic study in cynomolgus monkeys. Following administration of a single oral dose of 1 mg/kg ROF in monkeys, pharmacokinetic data for ROF and RNO was reported for the first time. After oral administration, ROF was rapidly absorbed and metabolized to its metabolite RNO. The mean area under the curve value of RNO was ~13 times larger than that of ROF, suggesting that most ROF was metabolized to RNO in cynomolgus monkeys.